An Exploration of the Key Indicators in Holistic Accountability at Public Sector Elementary Schools - Tahira Bibi; Sarah Warris (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2021)
Purpose: To ensure sustainable progress in education system accountability comes into play, prompting the researcher to undertake school accountability at   public sector elementary schools to gain insight into the prevailing accountability norms within public education as well as to gauge the applicability of a comprehensive model of Holistic Accountability. The study focused on the exploration of the four key indicators of holistic accountability at public sector elementary schools of Islamabad.   Design/Methodology/Approach: Qualitative descriptive approach was used to study of school accountability at public sector elementary schools within public education in the Federal Capital of Pakistan. Document analysis, Checklists and semi-structured interviews were conducted to collect the data. Findings: Study revealed an acceptance and need for adopting holistic accountability practices at elementary schools, along with transparency as regards to decision making, goal sharing and resource spending with the public. Implications/Originality/Value: This research study helps to contribute to the literature on school accountability and attempted to seek evidence whether holistic accountability can have some level of relevance in Pakistani context. The study helps to demonstrate the need to extend an understanding of western school accountability frameworks in juxtaposition with contextual complexities.